Clinical picture, diagnostics and treatment of bacterial meningitis - Sín, Robin; Struncova, Denisa; Cechurova, Lenka (Neuro-endocrinology letters, 2022)
Bacterial meningitis is a serious infectious disease of the cerebral meninges, which occurs worldwide and threatens the lives of people of all ages. The largest number of cases in developed countries is caused by the gram-positive bacterium Streptococcus pneumoniae. Other more common agents are Neisseria meningitidis serotype B and Listeria monocytogenes. Fever is the most commonly reported symptom in paediatric patients, occurring in up to 93% of cases. Further, it is possible to observe headache, vomiting and positive meningeal phenomena. The most common symptoms in adults are fever, headache, positive meningeal symptoms and impaired consciousness. Examination of cerebrospinal fluid is essential for the diagnosis of bacterial meningitis. The basis of treatment is the earliest possible administration of antibiotics, initially empirically and then purposefully according to the results. Corticosteroids, traditionally dexamethasone, are also used in therapy.
Keywords: horečka; dospělí; Listeria monocytogenes; Streptococcus pneumoniae; antibakteriální látky; Adult; lidé; Anti-Bacterial Agents; bolesti hlavy; dítě; Child; Humans; Meningitis, Bacterial; Fever; meningitida bakteriální; Headache